Quantifying Ground Deformation in the Los Angeles and Santa Ana Coastal Basins Due to Groundwater Withdrawal. Issue 5 (18th May 2018) - Riel, Bryan; Simons, Mark; Ponti, Daniel; Agram, Piyush; Jolivet, Romain
Abstract: We investigate complex surface deformation within the Los Angeles and Santa Ana Coastal Basins due to groundwater withdrawal and subsequent aquifer compaction/expansion. We analyze an 18 year interferometric synthetic aperture radar (InSAR) time series of 881 interferograms in conjunction with global positioning system (GPS) data within the groundwater basins. The large data set required the development of a distributed time series analysis framework able to automatically decompose both the InSAR and GPS time series into short‐term and long‐term signals. We find that short‐term, seasonal oscillations of ground elevations due to annual groundwater withdrawal and recharge are unsteady due to changes in seasonal withdrawal by major water districts. The spatial pattern of seasonal ground deformation near the center of the basin corresponds to a diffusion process with peak deformation occurring at locations with highest groundwater production. Long‐term signals occur over broader areas and are ultimately caused by long‐term changes in groundwater production. Comparison of the geodetic data with hydraulic head data from major water districts suggests that different regions of the groundwater system are responsible for different temporal components in the observed ground deformation. Short‐term, seasonal ground deformation is caused by compaction of shallower aquifers used for the majority of groundwater production whereas long‐term ground deformation is correlated with delayed compaction of deeper aquifers and potential compressible clay layers. These results demonstrate the potential for geodetic analysis to be an important tool for groundwater management to maintain sustainable pumping practices. Key Points: Groundwater pumping induces ground deformation on multiple spatial and temporal scales Different aquifer regions display distinct modes of deformation InSAR time series analysis reveals fine scale geologic structures and localized subsidence features